Three new species of the sac spider genus Clubiona Latreille, 1804 from the Yintiaoling Nature Reserve, Chongqing, China - Zhang, Xiang-Yun; Li, Zhao-Yi; Zhang, Zhi-Sheng (Zootaxa, 2025)
Three new species belonging to two species groups of the genus Clubiona Latreille, 1804 are described from the Yintiaoling Nature Reserve, Chongqing, China: C. lui sp. nov. (male) and C. yintiaoling sp. nov. (male) assigned into the C. corticalis species-group, C. tricuspidata sp. nov. (male, female) assigned into the C. pallidula species-group. Diagnoses, detailed descriptions and illustrations of these three species are provided.